C-C chemokine receptor-7 mediated endocytosis of antibody cargoes into intact cells - Charest-Morin, Xavier; Pépin, Rémy; Gagné-Henley, Angélique; Morissette, Guillaume; Lodge, Robert; Marceau, François (Frontiers in Pharmacology, 2013)
The C-C chemokine receptor-7 (CCR7) is a G protein coupled receptor that has a role in leukocyte homing, but that is also expressed in aggressive tumor cells. Preclinical research supports that CCR7 is a valid target in oncology. In view of the increasing availability of therapeutic monoclonal antibodies that carry cytotoxic cargoes, we studied the feasibility of forcing intact cells to internalize known monoclonal antibodies by exploiting the cycle of endocytosis and recycling triggered by the CCR7 agonist CCL19. Firstly, an anti-CCR7 antibody (CD197; clone 150503) labeled surface recombinant CCR7 expressed in intact HEK 293a cells and the fluorescent antibody was internalized following CCL19 treatment. Secondly, a recombinant myc-tagged CCL19 construction was exploited along the anti-myc monoclonal antibody 4A6. The myc-tagged ligand was produced as a conditioned medium of transfected HEK 293a cells that contained the equivalent of 430 ng/ml of immunoreactive CCL19 (average value, ELISA determination). CCL19-myc, but not authentic CCL19, carried the fluorophore-labeled antibody 4A6 into other recipient cells that expressed recombinant CCR7 (microscopy, cytofluorometry). The immune complexes were apparent in endosomal structures, colocalized well with the small GTPase Rab5 and progressed toward Rab7-positive endosomes. A dominant negative form of Rab5 (GDP-locked) inhibited this endocytosis. Further, endosomes in CCL19-myc- or CCL19-stimulated cells were positive for β-arrestin2, but rarely for β-arrestin1. Following treatment with CCL19-myc and the 4A6 antibody, the melanoma cell line A375 that expresses endogenous CCR7 was specifically stained using a secondary peroxidase-conjugated antibody. Agonist-stimulated CCR7 can transport antibody-based cargoes, with possible therapeutic applications in oncology.